The Implementation of Observe and Remember Game to Improve Vocabulary Mastery - Nurhikma; Ismail latief; Nanning (Inspiring: English Education Journal, 2020)
This research was aimed to see the improvement of vocabulary mastery students after learning process by using observe and remember game at the eighth grade students of SMPN 2 Cempa Kabupaten Pinrang. The results of the research are useful for the teacher and students. In this research, the researcher used pre-experimental method. The population of this research was the eighth grade SMPN 2 Cempa. The sample was one class VIII.3 consisted of 21 students. The sampling technique in this research used classroom random sampling. In collecting the data, the researcher used instrument in form vocabulary test consisted of matching and multiple choice questions in pre-test and post-test. The researcher collected the data through giving pre-test, treatment, and post-test. The researcher also gave questionnaire to know the responses of students to observe and remember game. Based on the calculation, the result showed that the mean score of pos-test (84,04) was higher than the mean score of pre-test (63,09) and obtained that α= 0,05 and (df) = N-1 = 21-1= 20, and the value of the t-table is 1,72472, while the value of t-test was 13,09. It means that the t-test value is greater than t-table (13,09≥1,72472). Thus it can be concluded that the vocabulary mastery students was better after getting the treatment. So, the null hypothesis(H0) was rejected and the alternative hypothesis (Ha) was accepted. The second result of analyzed data that 84.23 of the students were interested in using observe and remember game, in other word most of them interested to apply observe and remember game. Based on the research result, it was concluded that observe and remember game was improve students’ vocabulary mastery at the eighth grade of SMPN 2 Cempa.